Is Javanese still Vital in Plurilingual Societies of Karimunjawa? - Nirmala, Deli (Deskripsi Bahasa, 2018)
This paper aims at showing the vitality of Javanese in plurilingual societies in Karimunjawa. Karimunjawa is inhabited by fishermen from different ethnic groups like Maduranese, Buginese, Mandar. Observation, questionnaire, and interview with recording techniques were used to collect the data. The respondents are the students of Safinatul Huda junior and senior high schools and their parents who are interethnic marriage, living in Kemujan island. They were selected based on the availability principle that is due to their agreement for being interviewed. Besides, some interethnic-married couple in Karimunjawa were also interviewed, who were mostly aged citizens. Inferential method was used to analyzed data. The result indicates that Javanese is still actively used at home, schools, and mosques. Javanese is also learnt by non Javanese. They use Javanese since Javanese is the dominating one in Karimunjawa. There is a tendency that non-Javanese is shifting to Javanese and bahasa Indonesia, while Javanese is shifting to bahasa Indonesia. This indicates that Javanese is still strong even some of the non-Javanese tends to use Javanese not only its language but also its tradition like wedding ceremony.